(untitled) (Economic and Political Thought, 2013)
Human Resources Management (HRM) is essentially predetermined by the external determinants. The aim of the article is to focus on those processes whose substance and influence power create the utmost challenges for the HRM in the nearest and further future, and then show the alternative scenarios for dealing with problems they generate. Therefore, the attention is focused on the aging processes of the (Polish) society (as an effect of demographic changes), dematerialization of work (as an effect of technological changes) and financialization (as an effect of market changes). Two scenarios of HRM development are presented: the “economizing” one, which is a continuation of the reactions to global processes that are in progress (here: talent management, work flexibility, management by results) and the “humanistic” one, built of alternative approaches (here: diversity management, flexicurity, corporate social responsibility).